The Swiss‐Army‐Knife Self‐Assembled Monolayer: Improving Electron Injection, Stability, and Wettability of Metal Electrodes with a One‐Minute Proces. (11th February 2016) - Alt, Milan; Jesper, Malte; Schinke, Janusz; Hillebrandt, Sabina; Reiser, Patrick; Rödlmeier, Tobias; Angelova, Iva; Deing, Kaja; Glaser, Tobias; Mankel, Eric; Jaegermann, Wolfram; Pucci, Annemarie; et al.
Abstract : A novel Self‐assembled Monolayer (SAM) forming molecule bisjulolidyldisulfide (9, 9'‐disulfanediylbis(2, 3, 6, 7‐tetrahydro‐1H, 5H‐pyrido[3, 2, 1‐ij]quinoline)) is demonstrated which lowers the work function of metal surfaces by ≈1.2 eV and can be deposited in a 1 min process. Bisjulolidyldisulfide exists in a stable disulfide configuration prior to surface exposure and can therefore be stored, handled, and processed in ambient conditions. SAM from bisjulolidyldisulfide are deposited on metal surfaces (Au and Ag), including inkjet printed Ag on polyethylene terephthalate substrates, investigated by photoelectron and infrared spectroscopy, and used as electrodes in n‐type organic field effect transistor (OFET). Treatment of electrodes in OFET devices with with bisjulolidyldisulfide‐SAMs reduces the contact resistance by two orders of magnitude and improves shelf life with respect to pristine metal electrodes. The presented treatment also increases the surfaces wettability and thereby facilitates solution processing of a subsequent layer. These beneficial properties for device performance, processing, and stability, combined with ease of preparation and handling, render this SAM‐forming molecule an excellent candidate for the high‐throughput production of flexible electronic devices. Abstract : An ambient stable disulfide Self‐Assembled Monolayer‐forming molecule reduces the work function of metal electrodes by ≈1.2 eV and can be deposited from solution in 1 min. These monolayers have a strong effect on electron injection, improve surface wettability, device life time, and can be processed on printed silver electrodes.